Biostatistics : how it works - Selvin, Steve (Upper Saddle River, New Jersey : Pearson Education, 2004)
This concise, algebra-based text is a straight forward, clear approach to biostatistics, containing rigorous explanations of elementary methods without the (3z(Bbells and whistles(3y (Bassociated with other books that cover this topic. Its goal is to provide a sophisticated introduction of how statistics works at a beginning level. Every concept is carefully and clearly explained, enriched by a mathematical/statistical justification, and then illustrated by at least one concrete, worked data example. Beginning with basic concepts, the text allows readers to acquire the ability to understand rather complicated statistical issues, such as linear regression theory and application.s
I. Probability: Properties of samples -- 1. Descriptive statistics -- 2. Probability -- 3. Random variables -- 4. Probability distributions -- II. Statistics: Properties of sampled populations -- 5. Statistical inference I -- 6. Statistical inference II -- 7. Chi-square analysis -- 8. Linear regression -- 9. Correlation.
Includes bibliographical references (pages 381-383) and index.
Keywords: MEDICAL STATISTICS